2015
DOI: 10.1111/ijfs.12758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed electric field on selected properties of L‐tryptophan

Abstract: Summary The effects of pulsed electric fields (PEF) treatment on the solubility, surface tension and fluorescence spectra of L‐tryptophan were systematically investigated using a range of PEF intensities (0–50 kV cm−1) and a number of pulses (0–216). PEF frequency and pulse width used in this experiment were 1000 Hz and 40 μs, respectively. Under these conditions, the solubility, pH value and maximum relative fluorescence value (RFV) of L‐tryptophan were generally increased and then decreased with both increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Intrinsic fluorescence spectra assay was measured by the fluorescence characteristics of QWFH using the RF5300 fluorescence spectrophotometer (Shimadzu, Kyoto, Japan) (Zhang et al, ). Samples were 0.2 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsic fluorescence spectra assay was measured by the fluorescence characteristics of QWFH using the RF5300 fluorescence spectrophotometer (Shimadzu, Kyoto, Japan) (Zhang et al, ). Samples were 0.2 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The key benefit associated with the use of these techniques is improved nutritive value of food products due to the less thermal degradation of heat sensitive nutrients. Additionally, nonthermal food processing (Liu, Zeng, Sun, Han, & Aadil, ; Saeeduddin et al, ; Zhang et al, ) techniques also provide microbial safety to the food without thermal degradation (Grahl & Märkl, ). A wide range of studies has confirmed the potential of nonthermal processing methods to enhance the quality and shelf stability of various food products (Aadil, Zeng, Sun, et al, ; Aadil, Zeng, Wang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among nonthermal technologies, PEF (Lin et al ., ; Liu et al ., ; Zhang et al ., ; Wang et al ., ) have gained increasing attention in the food industry (Sampedro et al ., ), the excellent benefit of this technology beside the inactivation of micro‐organisms and enzymes (Zhao et al ., ), colour, flavour, (Barba et al ., ) aroma and nutritional properties of fruits and vegetables is preserved with high maintenance. Pulsed electric field treatment is a promising nonthermal pasteurisation technology for liquid food products aiming to inactivate micro‐organisms while maintaining heat‐sensitive bioactive components.…”
Section: Introductionmentioning
confidence: 99%